Analisis Kualitas Internet Financial Reporting pada Perusahaan BEI - Yunita Fatma Faidha; Emm Rani Nuristya; Yeni Kuntari (Jurnal Ilmiah Aset, 2026)
The development of digital transformation has encouraged companies to improve the quality of financial information disclosure through internet-based media or Internet Financial Reporting (IFR). Previous studies on IFR have mostly focused on the existence of IFR practices, internal company factors, or specific industrial sectors. Studies comparing IFR quality across industrial sectors while considering aspects of digital transparency, website quality, and Environmental, Social, and Governance (ESG) disclosure are still limited. This study aims to analyze the quality of Internet Financial Reporting among companies listed on the Indonesia Stock Exchange based on industrial sector classification. This research employs a quantitative approach using a descriptive comparative method. IFR quality is measured using an IFR index consisting of four components: content, timeliness, technology, and user support. Data analysis techniques include content analysis, descriptive statistics, and the Kruskal-Wallis Test. The results indicate that the manufacturing sector has a relatively higher average IFR quality compared to other sectors. However, the Kruskal-Wallis Test shows that the differences in IFR quality among industrial sectors are not statistically significant. The findings also reveal that the development of digital transformation has made digital transparency, website quality, and ESG disclosure important aspects in improving corporate reporting quality. This study is expected to provide contributions for companies and regulators in enhancing digital-based financial reporting transparency and quality in Indonesia.